2015
DOI: 10.1007/978-3-319-17344-3_6
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Lipid Membranes with Fibrillar Protein Aggregates

Abstract: Amyloid fibrils are an intriguing class of protein aggregates with distinct physicochemical, structural and morphological properties. They display peculiar membrane-binding behavior, thus adding complexity to the problem of protein-lipid interactions. The consensus that emerged during the past decade is that amyloid cytotoxicity arises from a continuum of cross-β-sheet assemblies including mature fibrils. Based on literature survey and our own data, in this chapter we address several aspects of fibril-lipid in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 135 publications
(152 reference statements)
0
6
0
Order By: Relevance
“…In contrast to these results, the use of gap junction inhibitors (CBX, MQ and 2-APB) successfully blocked soluble and insoluble (fibrillar) α-syn uptake in both neurons and oligodendrocytes. The lack of fibrillar uptake inhibition by peptide mimetics may in part be explained by the high affinity of fibrillar α-syn assemblies to cellular membranes [ 18 ], the selective binding of Cx32 to oα-syn, the limited efficacy of the Cx32 peptide sequences used (which may not target the region interest) and/or the half-life of the peptides within the cells. However, other mechanisms cannot be ruled out including an unidentified Cx that may be involved in the preferential uptake of fibrillar α-syn assemblies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to these results, the use of gap junction inhibitors (CBX, MQ and 2-APB) successfully blocked soluble and insoluble (fibrillar) α-syn uptake in both neurons and oligodendrocytes. The lack of fibrillar uptake inhibition by peptide mimetics may in part be explained by the high affinity of fibrillar α-syn assemblies to cellular membranes [ 18 ], the selective binding of Cx32 to oα-syn, the limited efficacy of the Cx32 peptide sequences used (which may not target the region interest) and/or the half-life of the peptides within the cells. However, other mechanisms cannot be ruled out including an unidentified Cx that may be involved in the preferential uptake of fibrillar α-syn assemblies.…”
Section: Discussionmentioning
confidence: 99%
“…This nucleation may happen when the monomer is associated with a membrane or in free solution and occurs during the lag phase of fibrillogenesis. It is a fundamental point that there are multiple pathways for fibril formation, many of which lead to fibrils with differing structural and morphological properties ( 14 , 18 , 26 , 27 ). The biologically relevant morphology may be different from one produced from a purified protein in vitro under a given set of conditions.…”
Section: Overview Of Amyloid Assemblymentioning
confidence: 99%
“…The biologically relevant morphology may be different from one produced from a purified protein in vitro under a given set of conditions. In many cases, it has been demonstrated that fibril formation is promoted following membrane binding of a protein monomer or a protein oligomer ( 14 , 28 , 29 , 30 , 31 , 32 ). This acceleration is generally attributed to a combination of factors, including the bound protein adopting a more favorable conformation for nucleation, the concentration of the protein into a small volume, and changing the process from one occurring in bulk solution to one that is effectively a 2-dimensional process ( 28 ).…”
Section: Overview Of Amyloid Assemblymentioning
confidence: 99%
See 2 more Smart Citations